Social Conflict in the Short Story ‘Ad-Dalīlu At-Tāih (The Lost Guide)’ by Najib Kailani (A Sociological Study of Karl Marx) - Lutfiana, Rima; Dewi, Intan Sari (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2023)
تحكي القصة القصيرة